Can prior instruction successfully alter the tackle type executed by a player?. Issue 4 (August 2021) - Edwards, Suzi; Tahu, Timana; Buchanan, Matthew; Tucker, Ross; Fuller, Gordon; Gardner, Andrew
The tackle is the in-game activity with the greatest risk for injury in collision sports. Qualitative match analysis has associated injury risk with tackle technique (e.g. tackle height, head position before contact). This exploratory study used gold-standard three-dimensional (3D) motion capture to investigate whether prior instructions to a tackler to execute different torso tackle types altered their tackle technique. Fifteen amateur-level rugby code players performed four sets of 10 tackle trials after instructions from an expert coach: two Australian National Rugby League (NRL) coaching manual instructions on upper and lower torso tackle height (UpperNRL, LowerNRL) ; and two novel variants that altered the tackler's contact with the ball carrier's upper torso ( UpperPop ) via a vertical 'pop action', or mid-torso ( MidTorso ) via increasing the contact height to the mid-torso. 3 D motion capture confirmed a favourable 'head up and forward' gaze focus on ball carrier before contact and a 'straight back' posture was more evident in UpperPop instruction than other instructions, with the least flexion for the head, trunk, trunk-pelvis, thoracolumbar and lumbopelvic (p < 0.01). MidTorso also attained a more optimal 'head up and forward' and a 'straight back' posture than a LowerNRL (p < 0.001). 'Leg drive on contact' revealed ankle, hip (p < 0.01) and thigh angles (p < 0.05) differences, likely to reflect the UpperPop 'pop action' instruction than other instructions. For coaches, this study demonstrated that amateur-level rugby-code players could follow instruction from an expert coach to execute tackling techniques within a session. Inclusion of tackle specific coaching instruction training program may be a viable injury reduction strategy.